Four new species of Lepanthes (Pleurothallidinae) from the southwestern Andes in Colombia - Moreno, Juan Sebastián; Galindo-Tarazona, Robinson; Alegría-Valencia, Melisa; Zuluaga Tróchez, Alejandro (Lankesteriana: International Journal on Orchidology, 2022)
Four new species of Lepanthes from the southwestern Andes of Colombia are described, illustrated and compared with morphologically similar species. The new species were found in San José del Salado, the Municipality of Dagua, Department of Valle del Cauca where several new species have been found and described in the past years.